PW 2825 Swim for safety sri lanka – survival swimming and water safety education among school children. (November 2018) - Ekanayaka, EMJSK; Birch, Rhiannon; Matthews, Bernadette; Nanayakkara, Asanka; Jayawardena, Mevan; Wijayaratne, Sanath; Dharmaratne, Samath D
Abstract : Introduction: 'Swim for Safety' is a recently introduced survival swimming and water safety training programme for Sri Lanka. The programme was developed by Sri Lanka Life Saving and Life Saving Victoria, Australia in response to the high drowning rate in Sri Lanka (4.4 per 1 00 000 population). The aim of the study was to determine changes in the survival swimming and water safety skills and knowledge of children aged 10–16 years following completion of the Swim for Safety programme. Method: The programme consists of 12 lessons (90 min per lesson), conducted over a 6–8 week period. It teaches the minimum skills required to survive an accidental fall into deep open water: safe entry and exit; roll into deep water; rotation and floating, sculling and treading water; and swimming in a controlled direction in any manner; as well as danger identification in and around water; safe rescue of a victim and basic emergency response. Changes in survival swimming and water safety skills were determined by pre- post study, with skills and knowledge tested prior to the first lesson and immediately following lesson twelve. Water safety knowledge was assessed via a self-administered questionnaire and skills were assessed by independent trained assessors. Results: Preliminary data is currently available for 768 students, with updated results reported at the conference. Comparison of the pre- and post-test results showed the substantial improvement of water safety knowledge and skills including: swim 25 m (2.2% pre-programme vs 73.3% pre-programme); float 2 min (0.9% vs. 65.9%); rotation in water (0.9% vs. 65.9%), perform a throw rescue (0.1% vs 58.3%) and sufficient water safety knowledge (52.6% vs 90.4%). Conclusion: The Swim for Safety programme effectively improves students' survival swimming and water safety skills and knowledge. Programme expansion will provide more students with lifelong skills that may ultimately reduce the drowning rate in Sri Lanka.